Adsorption of Co(II) from aqueous solutions onto Na-bentonite - Nguyễn Lê, My Linh; Nguyễn, Ngọc Thanh Vy (Hue University Journal of Science: Natural Science, 2025)
In this work, Na-bentonite was characterized by using X-ray diffraction (XRD), scanning electron microscopy (SEM), and nitrogen adsorption/desorption. Na-bentonite was used for the removal of Co(II) from aqueous solutions. Co(II) adsorption follows the pseudo-first-order kinetic model. The equilibrium data were analyzed based on the Langmuir and Freundlich adsorption isotherm models. The highest monolayer adsorption capacity for Co(II) at 303 K derived from the Langmuir equation is 25.25 mg/g on Na-bentonite. The obtained thermodynamic parameters demonstrate that the adsorption is spontaneous (∆G° < 0) and endothermic (∆H° > 0), with increased entropy (∆S° > 0) in the investigated temperature range.